The 20th Century’s Investigations of St. Thomas Aquinas’ Theory of Human Freedom (I) - Šulcienė, Lina (Problemos, 2001)
In this article, the author reviews some lines of research in St. Thomas Aquinas theory of human freedom in 20th century. Two basic lines of investigation are introduced. The first one considers Aquinas’ conception of natural law (the question of the status of his ethics) and has the presuppositions of his solution of the problem of human freedom in focus. The studies of this type put in question traditional Neo-Thomist view maintaining that Aquinas’ ethics is theory of natural law which it the basis of the free human actions, so that man’s practical decision is deducible from the first principles of natural law. The second line of investigation, introduced in this article, discusses Aquinas’ general theory of freedom and free human activity. The wide spectrum of problems is analysed, e.g., the problem of the structure of a free action, the problem of the relationship between will and intellect, as well as two widely discussed topics from Aquinas’ theory of freedom: intellectual determinism and voluntarism.